Debt and its use among Puerto Rican undergraduate students - Alice Abboud Chalhoub; Cristal Matos Corporán; Marisela Santiago Castro (Centro de Investigaciones Comerciales e Iniciativas Académicas, 2015)
Student debt in the United States has been quickly increasing during the past decade. As to the first quarter of 2014, the student loan debt surpassed credit cards debt and auto loans. Puerto Rico ranks #17 by total debt among the United States and territories. Nonetheless, students in Puerto Rico have an average of $18,000 of student debt,positioning it at the lowest rank by average debt. This paper explores the debt phenomena among Puerto Rican undergraduate students. Specifically, we want to determine if students have debt, and if so, what type and how they spend it. A sample of 194 undergraduate students from a School of Business at a public higher education institution of Puerto Rico was surveyed. Results indicate that 28% of business students have debt. Female students were more susceptible to have debt. Furthermore, top expenses covered by debt are food, education, car expenses, clothing, and entertainment. The results reveal that 90 percent is not receiving counseling about debt management from the financial aid office. From those receiving the financial advising (10 percent), only 2 percent perceive it as useful. These results provide an exploratory look into the debt and its use among Puerto Rican undergraduate students.